Peningkatan Kesadaran Hukum Pentingnya Perlindungan Data Pribadi Bagi Pekerja Migran Indonesia Di Hong Kong: Increasing Legal Awareness of the Importance of Personal Data Protection For Indonesian Migrant Workers in Hong Kong - Yuspin, Wardah; Azhari, Aidul Fitriciada; Wardiono, Kelik; Zuhdi, Syaifuddin; Kurnianingsih, Marisa; Marjanah, Iramadya Dyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Indonesia has passed Law No. 27 of 2022 on Personal Data Protection. However, this regulation is less effective in its implementation because it is hampered by supervisory institutions that have yet to be formed and will automatically impact the sanctioning mechanism. With the vulnerability of personal data theft that occurs in Indonesia, the urgency of this service is to provide insight into the protection of personal data and legal efforts made when personal data theft occurs to Indonesian Migrant Workers (PMI) in Hong Kong. The purpose of this community service is to increase legal awareness for workers because the condition of workers who have not returned to Indonesia for a long time may not understand the vulnerability of storing personal data in Indonesia because they are used to using personal data protection laws in Hong Kong which are robust and have been formed for a long time so that they are likely to experience culture shock when they return to Indonesia. The method used in this community service has two stages. The first stage is legal counseling for migrant workers in Hong Kong. The second stage is assisting with creating crisis centers both offline and online to assist PMI who intend to obtain information about personal data protection and victims who experience personal data theft.